2021
DOI: 10.21037/tcr-20-3294
|View full text |Cite
|
Sign up to set email alerts
|

Real-time and accuracy of rapid on-site cytological evaluation of lung cancer

Abstract: Background: Although using pathological diagnosis is the gold standard for lung cancer diagnosis, pathological reports take a long time. Rapid on-site assessment (ROSE) is a method to determine whether the quality of the specimens is sufficient for cytopathological diagnosis, which issues a preliminary report during the operation and takes shorter time. The aim of this study is to explore the clinical significance of rapid on-site evaluation (ROSE) in the diagnosis of lung cancer in terms of real-time and accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…ROSE is a widely used and effective diagnostic procedure during a needle aspiration biopsy of different organs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In the field of thoracic pathologies, several studies have demonstrated the utility of ROSE during both transbronchial and percutaneous needle aspiration techniques [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Even if some works failed to demonstrate that ROSE increases the sensitivity during cTBNA or EBUS-TBNA [ 15 , 16 ], there is robust evidence that ROSE may significantly reduce the need for additional passes and the complication rate, most importantly improving the adequacy of the samples addressed to molecular chacaterization of mandatory predictive biomarkers in non-small cell lung cancer [ 6 , 17 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROSE is a widely used and effective diagnostic procedure during a needle aspiration biopsy of different organs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In the field of thoracic pathologies, several studies have demonstrated the utility of ROSE during both transbronchial and percutaneous needle aspiration techniques [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Even if some works failed to demonstrate that ROSE increases the sensitivity during cTBNA or EBUS-TBNA [ 15 , 16 ], there is robust evidence that ROSE may significantly reduce the need for additional passes and the complication rate, most importantly improving the adequacy of the samples addressed to molecular chacaterization of mandatory predictive biomarkers in non-small cell lung cancer [ 6 , 17 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROSE may be performed during a cytology biopsy from any anatomic site. In the field of respiratory medicine, ROSE is commonly used during bronchoscopic sampling techniques (transbronchial fine needle aspiration, TBNA) or transthoracic fine needle aspiration (TTNA) of lung and/or mediastinum [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid on-site evaluation (ROSE) offers an approach to rapidly conduct cytomorphological characteristics of tissues obtained from biopsy procedures in order to gauge their adequacy and malignancy. ROSE procedures performed by experienced pathologists can contribute to improved LB diagnostic accuracy [ 10 ]. ROSE techniques have been frequently employed in the context of bronchoscopy-guided biopsy procedures [ 10 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…ROSE procedures performed by experienced pathologists can contribute to improved LB diagnostic accuracy [ 10 ]. ROSE techniques have been frequently employed in the context of bronchoscopy-guided biopsy procedures [ 10 15 ]. In contrast, there have been fewer studies regarding the application of ROSE approaches in the context of CT-guided LB [ 16 – 22 ].…”
Section: Introductionmentioning
confidence: 99%